Developing the Capacity of ESCWA Member Countries to Address the Water and Energy Nexus for Achieving Sustainable Development Goals - Nations Unies (United Nations, 2018)
This module highlights the utilization of Renewable energy (RE) to strengthen Water-Energy nexus. It addresses the utilization of RE commercialized technologies to improve water security by providing the power needed by water-related activities such as water distribution and wastewater treatment. Along the same lines, RE technologies can strengthen energy security and diversify national energy mix by providing energy sources that are less water intensive, availing modern energy services in the rural/remote areas, reducing dependence on fossil fuels sources of energy; hence contributing to the mitigation of greenhouse gases emission (GHG). These benefits are of much significance for the Arab countries in terms of the contribution to meet their growing demand on water and energy needs on one side and to realize sustainable development plans from the other side.